Pelatihan Penggunaan Software Bilog Untuk Analisis Butir Soal Bagi Guru-Guru SMA Plus Binabangsa Pekanbaru - Lilis Marina; Dedek Andrian; Astri Wahyuni (Community Education Engagement Journal, 2019)
This community service is motivated by many complaints of teachers who have difficulty in analyzing teacher-made questions to be used in evaluations. As a professional teacher we must make good questions and be able to analyze the questions to be used in the test. In addition, a teacher is also required to be proficient in using IT to support his work in the current era of globalization. Based on this, the community service needs to be held with the aim to assist teachers in preparing questions that are well used in evaluation. Long-term application of this activity is very beneficial for teachers and lecturers, teachers will be helped by the implementation of this service. For lecturers, this activity is needed as a form of implementation and fulfillment of Tridharma Perguruan Tinggi (Three Pillars of Higher Education). The form of activities carried out in this was training to use Bilog Software for questions analysis for Teachers of SMA Plus Binabangsa Pekanbaru. This service activity ran well which held in the odd semester of the 2019/2020 academic year at Binabangsa High School Plus. In this activity the teachers was very enthusiastic in participating, the lecturer was also enthusiastic in teaching Bilog Software for Question Analysis. From this activity the teacher was greatly helped in analyzing the questions and making the evaluation process successful.